On sensible fuzzy ideals of BCK-algebras with respect to a t-conorm - M. Akram; Jianming Zhan (International Journal of Mathematics and Mathematical Sciences)
We introduce the notion of sensible fuzzy ideals of BCK-algebras with respect to a t-conorm and investigate some of their properties. We give the conditions for a sensible fuzzy subalgebra with respect to a t-conorm to be a sensible fuzzy ideal with respect to a t-conorm. Some properties of the direct product and S -product of fuzzy ideals of BCK-algebras with respect to a t-conorm are also discussed.